Transforming society to meet the community needs and enhance the quality of life : a case study of Bishop Allard Vocational School - Matsoha, Francisca 'Mapitso (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.